As estratégias de implantação de sistemas integrados na Administração Pública: estudo aplicado ao projeto MASP - Sousa, Evelyne Cirilo (2018)
The present study analyzes the implementation strategies of the Integrated System of Huma Resources Management - SIGRH, object of the Modernization Project in the Administration of Services and Personnel Systems - MASP Project. Specifically, the studies identify the main characteristics of the strategies and / or guidelines for the implementation of the Enterprise Resource Planning - ERP, investigate the main difficulties and facilitators of the SIGRH implementation and identify the critical factors of the SIGRH implementation. The methodology used involved bibliographic research on strategy, government planning, enterprise resource planning, as well as documental research related to the MASP Project and its guidelines. The field research comprised interviews with key personnel of the MASP Project team, identified by their positions or experience within the Project analyzed. From the analysis of the data it was possible to verify that the SIGRH implementation process presented changes of guidelines that had repercussions on scope changes, noncompliance with deadlines, and lack of alignment among those involved. The results of the research indicate that a possible lack of support from top management, as well as the successive changes in scope that have occurred and deficiencies in the team's technical knowledge may have contributed to the problems of the implementation project. In this sense, significant modifications of the intended strategy for the implementation of the integrated solution were verified, which configured the design of emerging strategies built in the process of reformulation of the guidelines and scope of the project. Such remodeling resulted in a strategy implemented that diverged considerably from the intended strategy, which may have impacted on the unsuccessful outcome of the MASP Project, with the suspension of the implementation agreement.